2020
DOI: 10.1080/10408444.2020.1845119
|View full text |Cite
|
Sign up to set email alerts
|

Weight of evidence analysis of the tumorigenic potential of 1,3-dichloropropene supports a threshold-based risk assessment

Abstract: 1,3-Dichloropropene (1,3-D; CAS #542-75-6) is a fumigant used for preplant treatment of soil to control parasitic nematodes and manage soil borne diseases for numerous fruit, vegetable, field and tree and vine crops across diverse global agricultural areas. In the USA, 1,3-D has historically been classified by the U.S. EPA as likely to be carcinogenic to humans via both oral and inhalation routes. This classification for the oral route was primarily based upon increases in multiple tumor types observed in Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Other studies have found links between methyl bromide use and non‐Hodgkin’s lymphoma (Alavanja et al., 2014; Chiu et al., 2006) and stomach cancer (Barry et al., 2012). In contrast, other industry‐supported studies suggest that the fumigant 1,3‐dichloropropene, is applied at a level that should limit its risk of carcinogenicity (Driver et al., 2016; Yan et al., 2020). Similarly, there was also no association found between fumigant use and breast cancer in the wives of pesticide applicators (Werder et al., 2020), nor in glioma in the upper Midwest of the United States (Ruder et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found links between methyl bromide use and non‐Hodgkin’s lymphoma (Alavanja et al., 2014; Chiu et al., 2006) and stomach cancer (Barry et al., 2012). In contrast, other industry‐supported studies suggest that the fumigant 1,3‐dichloropropene, is applied at a level that should limit its risk of carcinogenicity (Driver et al., 2016; Yan et al., 2020). Similarly, there was also no association found between fumigant use and breast cancer in the wives of pesticide applicators (Werder et al., 2020), nor in glioma in the upper Midwest of the United States (Ruder et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…As stated above, 3‐CAA is also an in vivo metabolite of the fumigant 1,3‐dichloropropene. 1,3‐dichloropropene has been extensively investigated in vitro and in vivo for its genotoxic potential (Gollapudi et al, 1998 ; Stott et al, 2001 ; Badding et al, 2020 ; Yan et al, 2020 ). In vitro, the soil fumigant yielded mixed results.…”
Section: Introductionmentioning
confidence: 99%